Studi tentang Gaya Kepemimpinan dan Tingkat Pendidikan serta Pengaruhnya terhadap Kinerja Karyawan dalam Perspektif Islam - Cindy Maharati (FADZAT: Jurnal Ekonomi Syariah, 2021)
The purpose of this study was to examine and analyze the simultaneous, partial and dominant effect of the variable leadership style and education level on employee performance. This research is explanatory (explaining) is "to test the hypotheses of a cause-and-effect relationship between the symptoms (variables) being studied. The type of data used is the type of quantitative data which is quantified using a Likert scale. The research population is the employees of Rijan Mart Pacet Mojokerto. Data analysis used multiple linear regression. The results showed that: 1) Leadership style and level of education had a simultaneous effect on employee performance. 2) Leadership style has no partial effect on employee performance and education level partially affects employee performance 3) Education level has a dominant effect on employee performance. Limitations of the study: 1) The population of this study was taken at Rijan Mart Pacet Mojokerto. 2) The population and sample consisted of 32 employees of Rijan Mart Pacet Mojokerto. 3) Data collection is carried out on January 6 s.d. 6 February 2021. Research implications: The findings of this study will later reveal the leadership style and level of education that influence simultaneously and partially on employee performance and find variables that have a dominant influence on employee performance.